Advanced surgical technologies for lung cancer treatment: Current status and perspectives - Cai Hongfei; Wang Yonghui; Qin Da; Cui Youbin; Zhang Hongbo (Elsevier/KeAi Communications Co., 2025)
Lung cancer has become one of the key life-threatening factors and is the most common type of tumor. With the improvement of equipment and the improvement of lung cancer awareness, the surgical treatment of lung cancer is becoming more and more mature. Surgery can provide an important part of individualized treatment strategies for patients with different stages of lung cancer and different wishes. In addition, the concept of minimally invasive, precise, and intelligent has triggered a revolutionary change in the surgical treatment strategy for lung cancer. Therefore, this review focuses on the development of lung cancer surgery history, summarizing the era from traditional surgery to the era of minimally invasive thoracic surgery based on TV-assisted thoracic surgery. The operating methods and treatment effects of different surgical methods are comprehensively introduced, and the optimization and improvement of different surgical methods in the future are also discussed. Along with the concept of minimally invasive surgical techniques, there are more and more explorations of nanotechnology in the surgical treatment of lung cancer. The application of nanotechnology in lung cancer imaging, and the combination of surgery with nanomedicine is an effective solution for cancer treatment today. So, this review also summarizes the application prospects of nanotechnology before, during and after lung cancer surgery.